ILMU PENGETAHUAN AGAMA DAN ILMU UMUM - Wirdatul Hasanah; Siti Muthiatun Najiah; Firda Maghfirotus S; Futuh Muafi; Muhammad Hori (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Religious knowledge and general science are two essential fields that play a significant role in shaping individuals who are intellectually competent, morally grounded, and capable of adapting to the rapid changes of the modern world. In contemporary education, integrating these two disciplines has become increasingly important, as a segregated approach often leads to fragmented perspectives among students. Religious knowledge provides moral, ethical, and spiritual foundations that guide human behavior, while general science offers empirical, rational, and practical insights necessary for addressing social, technological, economic, and environmental challenges. An interdisciplinary approach between these knowledge fields aims not only to eliminate the long-standing dichotomy within the educational system but also to build a more holistic mindset. Through this integration, students are able to recognize that religion and science are not opposing entities, but complementary sources of truth and understanding. This study highlights the urgency of integrating religious and scientific knowledge and emphasizes its benefits in producing a generation with balanced intellectual, emotional, and spiritual intelligence. The findings suggest that such an integrative approach enhances learning quality and supports the comprehensive development of students.